'Venecie due sunt’: Venice and its grounding in the Adriatic and North Italian background - West-Harling, V (Brepols Publishers, 2013)
The years 888-962 are a period in which the Kingdom of Italy was not ruled by kings from across the Alps, the only such period from the end of the eighth century to the end of the eleventh. They were for a long time accepted as a period of major political breakdown and failure, and, in north-central (not southern) Italy, the start of the long run in to the early city communes and Italy’s future history as a radically disunited peninsula. In the light of not only recent historical reanalyses but also the emergence of a large quantity of archaeological data, this image can be tested, and in this book is, by both historians and archaeologists. A far more subtle and nuanced picture emerges from the interdisciplinary work in this volume. This book will be an essential starting-point for all future work on Italy in this period.